Virtual Identity of Urban and Rural Muslim Youth - Fajrie, Mahfudlah; Muhammad Nashrul Haqqi; Akhmad Pandhu Wijaya; Agung Nugroho (MOZAIK HUMANIORA, 2024)
This research discusses the virtual identity of urban and rural Muslim teenagers. The method used is virtual ethnography, data collection techniques using documentation, interviews and observation. The research results show that cyber religion between urban and rural teenagers is not much different. Muslim teenagers often consume content or information on digital platforms. For urban Muslim teenagers, matters of religious activity are not for public consump-tion, but are instead private matters. This is different from Muslim teenagers in villages, who not only consume but also produce religious content because the majority of teenagers in villages have a background as alumni of Islamic boarding school students, so they already have sufficient religious knowledge, so they have the courage to produce religious content, this is This is also done as a form of broadcasting or preaching Islam as well as representing themselves as Muslim teenagers. From the cyber religion model of Muslim teenagers, both urban and rural, it shows that the religious identity formed and represented by teenagers shows liquidity, where teenagers want to be known as free, fluid individuals, even for religious activities, where with information technology this becomes easier. and practical.